2007
DOI: 10.1139/e07-039
|View full text |Cite
|
Sign up to set email alerts
|

The relative influence of Laurentide and local ice sheets during the last glacial maximum in the eastern Chic-Chocs Range, northern Gaspé Peninsula, Quebec

Abstract: Geochemical signatures, erratic dispersal, and striae indicate glacial flows in the north-central Gaspé Peninsula exclusively from Appalachian sources, except for the coastal fringe. During the last glacial maximum (LGM), ice from the Monts McGerrigle flowed northward and northwestward over the summits of the eastern Chic-Chocs Range and the coastal plateau to the Gulf of St. Lawrence. Lesser flows also occurred to the north from Mont Albert and the western Chic-Chocs Range. Where intersecting striae were note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Sirois and Grandtner, 1992;Martin and Germain, 2016) contrasting with the generally dense forest cover found over most of the amphibolite du diable. Exposure of the metamorphic sole is further restrained by the presence of numerous boulders of both local and remote origin related to the last glacial maximum (see Olejczyk and Gray, 2007). Consequently, exposed sections through the metamorphic sole are not continuous over scales of hundreds of metres as in Oman, complicating the study of mineralogical changes with distance to the contact of the peridotite, as folding and possible late faulting cannot be rigorously evaluated.…”
Section: Nature Structure and Deformation Of The Solementioning
confidence: 99%
“…Sirois and Grandtner, 1992;Martin and Germain, 2016) contrasting with the generally dense forest cover found over most of the amphibolite du diable. Exposure of the metamorphic sole is further restrained by the presence of numerous boulders of both local and remote origin related to the last glacial maximum (see Olejczyk and Gray, 2007). Consequently, exposed sections through the metamorphic sole are not continuous over scales of hundreds of metres as in Oman, complicating the study of mineralogical changes with distance to the contact of the peridotite, as folding and possible late faulting cannot be rigorously evaluated.…”
Section: Nature Structure and Deformation Of The Solementioning
confidence: 99%
“…The Baie des Chaleurs was marine inundated by 12,600 ±200 cal yrs BP (Olejczyk and Gray, 2007) following deglaciation and retreat of the Gaspesie (Olejczyk and Grey, 2007) and Escuminac ice caps (Pronk et al, 1989;Bail, 1985) and the eastern limit of the LIS. After reaching a postglacial marine limit of 45 to 55 m on the north shore of the Baie des Chaleurs (Veillette and Cloutier, 1993), RSL dropped below the present-day level around 12,000 cal yrs BP (Thomas et al, 1973).…”
Section: Regional Physiographymentioning
confidence: 99%
“…Hétu and Gray (1985) suggested that the plateaus could have been exposed during the Wisconsin glaciation as well because they only found slight traces of glacial erosion and the age of these erosion events cannot be determined accurately because of the lack of correlative deposits. However, the nunatak hypothesis is controversial (Wynne-Edwards 1937;Marie-Victorin 1938;Griggs 1940;Scoggan 1950;Rousseau 1974;Olejczyk and Gray 2007). For example, Olejczyk and Gray (2007) postulated that the sparse striae and erratics on the plateaus may have been due to protection from the glaciers by an initial buildup of ice.…”
Section: Introductionmentioning
confidence: 99%
“…However, the nunatak hypothesis is controversial (Wynne-Edwards 1937;Marie-Victorin 1938;Griggs 1940;Scoggan 1950;Rousseau 1974;Olejczyk and Gray 2007). For example, Olejczyk and Gray (2007) postulated that the sparse striae and erratics on the plateaus may have been due to protection from the glaciers by an initial buildup of ice. Although it is uncertain if the Chic-Chocs were nunataks, they still contain numerous endemic and disjunct populations of vascular plants (Fernald 1925), lichens (Macoun 1902;Dodge 1926;Sirois et al 1988;McMullin et al 2014), and moss (Belland 1987a(Belland , 1987b(Belland , 2015, many of which typically occur in the Arctic and the western mountains of North America.…”
Section: Introductionmentioning
confidence: 99%